Puddle wonderful : poems to welcome spring - Katz, Bobbi (New York : Random House, 1992)
A collection of poems about the many aspects of spring and spring holidays, by such poets as E. E. Cummings, Eve Merriam, Jack Prelutsky, Lillian Moore and Dennis Lee.
Keywords: Spring -- Juvenile poetry; Children's poetry; Poetry collections